Pemanfaatan Roda Misteri dalam Pembelajaran Fikih di MIN 9 Banda Aceh - Syukriani, Syukriani; Widyanto, Anton; Gade, Fithriani; Masykur, Masykur (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Active student learning with the principle that students must be actively involved in every learning process, one of which is the Learning Media in the form of the Mystery Wheel. The purpose of this study was to determine the planning, utilization and advantages and disadvantages of using the Mystery Wheel media in learning Jurisprudence at MIN 9 Banda Aceh. This research was conducted with a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews, observation and documentation. The results of the study show that planning Fikih lessons using the Mystery Wheel media at MIN 9 Banda Aceh is planned by including the Mystery Wheel media in the core part of the lesson plan. The use of the Mystery Wheel media in learning Jurisprudence at MIN 9 Banda Aceh the Mystery Wheel media is carried out by the teacher preparing lesson plans using the Mystery Wheel media, preparing the material to be taught using the Mystery Wheel media, preparing cards containing the material to be taught and the teacher attaches the material in the first layer on the Mystery Wheel. Then students take the card with the same content as shown by the needle and students express their opinions in front of the class. The advantages of the Mystery Wheel media can increase student enthusiasm in learning and also make learning not boring, so students can easily understand learning, while the drawback is that the Mystery Wheel media is still used manually so it cannot be used for digital classes.